HIRSCHKOP, Ken. The Cambridge Introduction to Mikhail Bakhtin. Cambridge, United Kingdom; New York, NY: Cambridge University Press, 2021, 194p. E-book. (Series: Cambridge introductions to literature) - Gomes, Filipe Almeida (Bakhtiniana. Revista de Estudos do Discurso, 2023)
Resenha